2017
DOI: 10.1002/jez.2073
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and concentration of maternal progesterone in the yolk of Greater Rhea eggs (Rhea americana)

Abstract: Progesterone is the most concentrated maternal yolk steroid characterized to date in birds; however, no information about it is available in ratite eggs. We collected freshly laid eggs from zoo-housed Greater Rhea females (Rhea americana) bred under similar rearing conditions during two breeding seasons to characterize concentration and distribution of maternal yolk progesterone. After high-performance liquid chromatography analysis, yolk hormone was measured using a commercial electrochemiluminescence immunoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(71 reference statements)
1
2
0
Order By: Relevance
“…In the Greater Rhea , we previously found that yolk hormone deposition varies among eggs of different captive populations and could influence the chicks' physiology and behavior (Della Costa et al, 2019). We also found that yolk hormone levels did not vary when the rearing conditions remain similar thorough the years (Della Costa et al, 2017). However, it is unknown whether Greater Rhea females could modify yolk hormone deposition when the social environment changes.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…In the Greater Rhea , we previously found that yolk hormone deposition varies among eggs of different captive populations and could influence the chicks' physiology and behavior (Della Costa et al, 2019). We also found that yolk hormone levels did not vary when the rearing conditions remain similar thorough the years (Della Costa et al, 2017). However, it is unknown whether Greater Rhea females could modify yolk hormone deposition when the social environment changes.…”
Section: Introductionsupporting
confidence: 60%
“…Other factors related to the females' state (e.g., age, physical condition, and past experiences) have changed over the years. However, we previously reported that yolk corticosterone and progesterone did not vary between the laying seasons when the Greater Rhea females are maintained under similar captive conditions (Della Costa, 2018; Della Costa et al, 2017). Thus, it is not expected that yolk hormone deposition varies with females aging within reproductive years.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation